Portable spectroscopic fast neutron probe and 3He detector dead-time measurements. (September 2016) - Akyurek, T.; Tucker, L.P.; Liu, X.; Usman, S.
Abstract: This paper presents dead-time calculations for the Portable Spectroscopic Fast Neutron Probe (N-Probe) using a combination of the attenuation law, MCNP (Monte Carlo N-particle Code) simulations and the assumption of ideal paralyzing and non-paralyzing dead-time models. The N-Probe contains an NE-213 liquid scintillator detector and a spherical 3 He detector. For the fast neutron probe, non-paralyzing dead-time values were higher than paralyzing dead-time values, as expected. Paralyzing dead-time was calculated to be 37.6 μs and non-paralyzing dead-time was calculated to be 43.7 μs for the N-Probe liquid scintillator detector. Dead-time value for Canberra 3 He neutron detector (0.5NH1/1K) was also estimated using a combination of subcritical assembly measurements and MCNP simulations. The paralyzing dead-time was estimated to be 14.5 μs, and the non-paralyzing dead-time was estimated to be 16.4 μs for 3 He gas filled detector. These results are consistent with the dead-time values reported for helium detectors. Highlights: Dead-time of Liquid scintillator detector was calculated. He detector dead-time estimation was obtained using MCNP code and subcritical assembly. Attenuation law, paralyzing and non-paralyzing dead-time models combined. Results are consistent with the dead-time values reported for helium detectors.